Examining the effect of virtual reality therapy on cognition post-stroke: a systematic review and meta-analysis. (2nd January 2022) - Wiley, Elise; Khattab, Shereen; Tang, Ada
Abstract: Introduction: Virtual reality (VR) are user-computer interface platforms that implement real-time simulation of an activity or environment, allowing user interaction via multiple sensory modalities. VR therapy may be an effective intervention for improving cognitive function following stroke. The aim of this systematic review was to examine the effectiveness of exercise-based VR therapy on cognition post-stroke. Methods: Electronic databases were searched for terms related to "stroke", "virtual reality", "exercise" and "cognition". Studies were included if they: (1) were randomized-controlled trials; (2) included VR-based interventions; (3) included individuals with stroke; and (4) included outcome measures related to cognitive function. Data from included studies were synthesised qualitatively and where possible, random effects meta-analyses were performed. Results: Eight studies involving 196 participants were included in the review, of which five were included in meta-analyses ( n  = 124 participants). Studies varied in terms of type (combination of VR therapy and conventional therapy, combination of VR therapy and computer-based cognitive training, VR therapy alone) and duration of interventions (20–180 min), sample size ( n  = 12–42), length of the interventions (4–8 weeks), and cognitive outcomes examined. VR therapy was not more effective than control for improving global cognition ( n  = 5, SMD = 0.24, 95%CI:−0.30, 0.78, p  = .38), memory ( n  = 2 studies, SMD= 0.00, 95%CI: −0.58, 0.59, p  = .99), attention ( n  = 2 studies, MD = 8.90, 95%CI: −27.89, 45.70, p  = .64) or language ( n  = 2 studies, SMD = 0.56, 95%CI: −0.08, 1.21, p  = .09). Conclusion: VR therapy was not superior to control interventions in improving cognition in individuals with stroke. Future research should include high-quality and adequately powered trials examining the impact of virtual reality therapy on cognition post-stroke. Implications for rehabilitation: Virtual reality therapy is a promising new form of technology that has been shown to increase patient satisfaction towards stroke rehabilitation. Virtual reality therapy has the added benefits of providing instant feedback, and the difficulty can be easily modified, underscoring the user-friendliness of this form of rehabilitation. Virtual reality therapy has the potential to improve various motor, cognitive and physical deficits following stroke, highlighting its usefulness in rehabilitation settings.